2011
DOI: 10.1142/s0192415x11008798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Tai Chi Practice on Balance and H-Reflex Characteristics

Abstract: The purpose of the present study was to examine the effects of long-term Tai Chi practice on postural balance and H-reflex. Sixteen healthy volunteers, eight with three or more years of experience in Tai Chi training (Tai Chi Group-TCG), and eight with no experience in Tai Chi training (Control Group-CG) participated in the study. Postural sways were measured under four experimental conditions: (1) Standing still with eyes open (EO); (2) Standing still with eyes closed (EC); (3) Standing and turning head to le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 39 publications
6
21
0
Order By: Relevance
“…more people in this group had practiced Tai Chi before. This is consistent with other reports of longterm benefits of Tai Chi (Guan & Koceja, 2011).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…more people in this group had practiced Tai Chi before. This is consistent with other reports of longterm benefits of Tai Chi (Guan & Koceja, 2011).…”
Section: Discussionsupporting
confidence: 94%
“…It is characterized by slowness, gentleness, grace, and constant weight shifting (Mao, Hong, & Li, 2006). The effectiveness of Tai Chi practice on fall prevention has been documented by various studies; Tai Chi has shown positive effects on older adults' balance (Chen, Fu, Chan, & Tsang, 2012;Guan & Koceja, 2011;Guo et al, 2014), gait (Guan & Koceja, 2011), flexibility (Park & Song, 2013), fear of falls (Park & Song, 2013), and fall rates (F. Li, Harmer, Fisher, & McAuley, 2004). Thus, the CDC (2013) has recommended Tai Chi among a variety of exercises as an effective strategy for fall prevention in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it could improve strength, proprioception, psychological well-being, and balance [1822]. In addition, many researches also demonstrated the effectiveness of TC in reducing the risk of falls for elderly people [19, 20]. For example, Guan and Koceja observed that the postural sway of the TC group was less significant than the control group during standing [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many researches also demonstrated the effectiveness of TC in reducing the risk of falls for elderly people [19, 20]. For example, Guan and Koceja observed that the postural sway of the TC group was less significant than the control group during standing [19]. For another example, Li and Manor indicated that TC exercise increased functional gait and leg strength performance among people with peripheral neuropathy [21].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of sensory fibers can result from either a passive or an active movement as well as from externally applied mechanical or electrical stimuli (Hultborn et al 1996;Earles et al 2002aEarles et al , 2002b. The fact that the inhibitory effect of electrically induced HD is altered in clinical populations (Huang et al 2006) and appears amenable to training interventions (Guan and Koceja 2011;Hoseini et al 2011) provides an important clinical rationale for understanding and characterizing the mechanism and outcomes associated with HD.…”
Section: Introductionmentioning
confidence: 99%